1991
DOI: 10.1111/j.1365-2249.1991.tb05703.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of intravenous immunoglobulin in patients with severe inflammatory chest disease and IgG3 subclass deficiency

Abstract: SUMMARYTo investigate the efficacy of i.v. IgG treatment in pediatric patients with inflammatory lung disease, a prospective, controlled clinical trial was carried out over a 2-year study period. Patients were enrolled on the basis of severe clinical symptomatology. After 1 year of conventional treatment, the patients received 400 mg/kg per month of an i.v. IgG product containing only trace amounts of IgG3 in addition to their regular treatment throughout the second year. Significant clinical improvement, as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Several studies have demonstrated that IgG subclass deficiency and impairment of antibody production are frequent findings in this group of patients [19,20]. In our early studies IgG3 deficiency was the most common [18].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have demonstrated that IgG subclass deficiency and impairment of antibody production are frequent findings in this group of patients [19,20]. In our early studies IgG3 deficiency was the most common [18].…”
Section: Discussionmentioning
confidence: 98%
“…CRS may be related stronger to allergy than to humoral immunologic defect and ongoing allergic inflammation may contribute to sinus pathology. The group of children with IgG3 subclass deficiency, upper and lower respiratory tract infections with bronchitis and severe steroid-dependent asthma was studied [19]. During the first year of observation patients received conventional treatment with antibiotics and antiasthmatics.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between IgG3 responses and improved infectious disease outcomes have also been observed for chikungunya and plasmodium infection [15,[18][19][20][21], among others. Furthermore, individuals with reduced or deficient serum levels of IgG3 tend to have recurrent upper respiratory infections [22][23][24][25]. Collectively, these clinical associations and subclass switch experiments suggest the functional importance of the IgG3 subclass.…”
Section: Introductionmentioning
confidence: 94%
“…A sample size of 21 had 80% power at a 5% level of significance to detect differences in the proportion of asthma exacerbations before and after treatment, based on previous data. 17 To allow for the possibility of up to 30% of participants withdrawing early from the study, a recruitment target of 30 participants was set. The intention-to-treat (ITT) population comprised all subjects who received at least 1 IVIG infusion; the per-protocol (PP) population comprised the subjects in the ITT population without full protocol deviations.…”
Section: Methodsmentioning
confidence: 99%